IIUM Moringa technology for water treatment and ready-to-use therapeutic food for the treatment of malnutrition - Jami, Mohammed Saedi; Alam, Md Zahangir; Mohd. Salleh, Hamzah; Jamal, Parveen; Kabbashi, Nassereldeen Ahmed; Shahbuddin, Munira; Mohd. Nasir, Fatin Zulaikha; Mohd Hijab, Nadzihah (2019)
A new natural, environmentally friendly, safe, and sustainable phytodisinfectant from Moringa oleifera seed to be used in water and wastewater treatment. Both qualitative and quantitative susceptibility testing has shown that Moringa-based phytodisinfectant can inhibit both gram-negative as well as gram-positive microorganisms. The methodology to be employed involves application of the best method of seed processing on the disinfection property of Moringa oleifera seeds extract and mode of microbial attack which was developed in the earlier project. Prototype Development Research Grant Scheme (PRGS) in collaboration with the Ministry of Higher Education which is a pre commercialization pilot scale plant development. This product can be applied to surface water treatment for small to medium size communities, mobile water treatment system for natural disaster areas e.g. flood, earthquake, hurricane, tsunami, drought etc and to assist with the management of public health in shelters, war and refugee camps. It can be used in households and at community levels and use in emergency situations where there is urgent need to disinfect water. Its wide range of marketability is available for drinking water companies or agencies. This invention brings job opportunities for farmers to cultivate Moringa oleifera trees as a cash crop for the sale of dry seeds to processing companies. It has commercial potential to be marketed as coagulants and Phytodisinfectants to interested countries, to reduce the use of harmful chemicals in the environment.